Procedural and outcome impact of obesity in cryoballoon versus radiofrequency pulmonary vein isolation in atrial fibrillation patients. (19th May 2022) - Scheurlen, C; Van Den Bruck, JH; Dittrich, S; Erlhoefer, S; Filipovic, K; Lueker, J; Woermann, J; Steven, D; Sultan, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cryoballoon-(CB)- and radiofrequency-(RF)-ablation are the most common techniques for pulmonary vein isolation (PVI) in patients (pts) with symptomatic atrial fibrillation (AF). An increasing number of pts undergoing PVI are obese. Objective: To address the paucity of procedural differences and outcome data of CB- vs. RF-based PVI in relation to body mass index (BMI) of AF patients. Methods: All pts undergoing de novo PVI between 01/2018-08/2019 at our university hospital were included in this retrospective analysis. Pts of each group (CB-PVI vs. RF-PVI) were subdivided based on their BMI: normal weight BMI <25kg/m², pre-obesity 25-30kg/m², obesity stage I 30-35kg/m² and severe obesity stage II ≥35kg/m². Hereafter, procedural characteristics and AF recurrence rate during follow-up were compared with regard the different BMI groups. Results: A total of 526 pts (62% male, 65.3±11.2 years) underwent successful de novo PVI (320 CB and 206 RF). Especially in obese patients, differences in procedural characteristics were noted: A significantly increased contrast medium volume in CB group (all: CB 50 [40-80] vs. RF 20 [20-30], p<0.001; BMI≥35: CB 70 [54.5-102.5] ml vs. RF 20 [15-30] ml, p<0.001). In line with previous studies, the overall procedure time was significantly shorter with CB-PVI (CB 75 [60-100] vs. RF 120 [110-180], p<0.001). Also, as expected, lower fluoroscopy dose was detected in RF group (all: CB 392.4 [197.9-995.9] vs. RF 282.5 [139.8-507.2], p<0.001). The complication rate was equal throughout all BMI groups. A 12-month follow up was available in 480 of 526 (91%) pts. Freedom from any arrhythmia was comparable between CB-PVI and RF-PVI (CB 77% vs. RF 75%, p=0.63). However, for obese pts a trend towards higher AF recurrence rate after RF- compared to CB-PVI was observed (BMI≥35: CB 24% vs. RF 50%, p=0.099). Conclusion: For obese pts CB-PVI is similarly safe and effective as RF-PVI. The significantly shorter procedure time for CB-PVI may minimize potential obesity-related complications. However, the lower contrast medium quantity and fluoroscopy dose in RF-PVI must be considered. AF recurrence rates were comparable between CB-PVI und RF-PVI. Randomised trials are needed to evaluate the long-term freedom of AF recurrence in pts with higher BMI comparing CB- vs. RF-based PVI and possible obesity related complication.